P-65 A hospice virtual ward – Providing complex palliative care in the community. (19th November 2022) - Curran, Emily; Marshall-Pallister, Julie; Kane, Chris
Abstract : Community palliative care has evolved in intensity and complexity, with more desire from patients and families to remain at home. We wanted to determine whether a virtual ward model would be beneficial to our patients, and therefore set up a 6 month pilot. The aim was to provide a responsive, enhanced multidisciplinary specialist palliative care service to manage complex and acute needs in the community, for patients felt to be at high risk of in-patient admission. The model was based around a daily multidisciplinary team meeting consisting of palliative medicine doctors, nurses, allied health professionals and family support workers. A plan of care was made in the meeting and the patient assessed at home by the most appropriate member(s) of the team. In the virtual ward pilot we had 36 patient admissions. At the initial review 26 of the patients were in the unstable phase of illness and 6 were deteriorating, highlighting that the virtual ward helped patients with complex acute needs. Preferred place of care was maintained in 31 patients (86%) and preferred place of death was maintained in 12 out of 14 patients who died (86%). Hospital or in-patient hospice stay was likely avoided in 14 patients. Supported therapies included bisphosphonate infusions, ascitic paracentesis, and non-invasive ventilation titration and withdrawal. The virtual ward has enabled patients to have complex symptom management, therapy reviews and psychosocial support in the place of their choice, helping to support their preferred place of care and death as well as avoiding unnecessary admissions. NHS England & Improvement has asked all Integrated Care Systems to extend or introduce virtual ward models (NHS E&I. Supporting information for ICS leads. Enablers for Success: virtual wards including hospital at home. April 2022. [Internet]). Our pilot has shown that virtual ward models can be used effectively and help manage the increasing demand on palliative care services.